Cost Analysis of Promotion Mix to Increase Sales - Nurlina; Baharuddin Semmaila; Moh. Zulkifli Murfat (Jurnal Manajemen Bisnis, 2021)
The aim of this research is to find out how much costs are incurred in the promotion mix PT Sungai Budi Group increases sales; examines the promotion mix, the most dominant increase in sales. The method of observation, library research, interview, are the research methods used in this study. The multiple linear regression method is the analytical method employed. The study was carried out at PT Sungai Budi Group in Makassar. Multiple linear regression with SPSS 20 was used to analyze the data. The result shows that mixed advertising, promotion and advertising have a positive influence on sales growth.